MiR-147b-3p promotes osteogenesis by targeting NDUFA4 and PI3K/AKT pathway - Yuanyuan Guo; Kai Shen; Zhijie Li; Changchun Niu; Yang Luo (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteoporosis (OP) is a progressive metabolic bone disease characterized by impaired bone microarchitecture, decreased bone strength, and dysregulated bone remodeling, leading to an increased risk of fractures. Among osteoporotic fractures, osteoporotic vertebral compression fractures (OVCF) are the most common and can significantly impact patients’ quality of life. Growing evidence suggests that microRNAs (miRNAs) play a crucial role in bone homeostasis by regulating osteoblast differentiation, bone metabolism, and remodeling processes. Notably, miR-147b-3p has been found to be downregulated in OVCF; however, its specific role in osteogenic regulation remains largely unknown. Therefore, further investigation is warranted to elucidate the function and underlying mechanism of miR-147b-3p in osteogenic differentiation. Methods The GSE93883 and GSE74209 datasets were retrieved from the Gene Expression Omnibus (GEO) database to investigate specific microRNAs involved in the regulation of osteogenesis. Differential expression of miR-147b-3p and NDUFA4 was assessed between healthy controls and patients with osteoporotic vertebral compression fractures (OVCF) using real-time quantitative PCR.To modulate the expression levels of miR-147b-3p in MC3T3-E1 cells, both the miR-147b-3p mimic and inhibitor were utilized. Cell viability was evaluated via the CCK-8 assay to assess the impact of miR-147b-3p on MC3T3-E1 cell proliferation. Real-time PCR and Western blot analysis were conducted to quantify the expression levels of osteogenic markers across different experimental groups. Alizarin red staining (ARS) was employed to examine the effect of miR-147b-3p on the mineralization capacity of MC3T3-E1 cells. In vivo experiments were performed to evaluate the functional role of miR-147b-3p. Bioinformatics databases were used to predict the potential target gene of miR-147b-3p (NDUFA4), and the predictions were validated by a dual luciferase reporter gene assay.To investigate the regulatory role of the miR-147b-3p/NDUFA4 axis in osteogenic differentiation, MC3T3-E1 cells were transfected with the NDUFA4 overexpression plasmid and miR-147b-3p mimic. Western blot analysis was performed to assess the phosphorylation levels of PI3K and AKT, in order to explore whether the miR-147b-3p/NDUFA4 axis regulates osteogenic differentiation through the PI3K/AKT signaling pathway. Results Our results indicated a significant downregulation of miR-147b-3p and a concurrent upregulation of NDUFA4 in patients with osteoporotic vertebral compression fractures (OVCF). A luciferase reporter assay confirmed that NDUFA4 is a direct target gene of miR-147b-3p.To examine the functional role of miR-147b-3p, both in vitro and in vivo experiments were conducted.The experimental findings revealed that the miR-147b-3p mimic significantly enhanced cell viability, increased protein expressions of Alkaline Phosphatase (ALP) and Runt-related Transcription Factor 2 (RUNX2), and promoted mineralization as evidenced by Alizarin Red S staining. Conversely, treatment with the miR-147b-3p inhibitor or overexpression plasmid for NDUFA4 (pNDUFA4) produced opposite effects.Furthermore, the miR-147b-3p/NDUFA4 axis was found to regulate the PI3K/AKT signaling pathway.The miR-147b-3p mimic significantly increased the phosphorylation levels of PI3K (p-PI3K) and AKT (p-AKT), whereas pNDUFA4 led to their reduction. Conclusions This study demonstrated that miR-147b-3p plays a crucial role in promoting osteogenic differentiation in osteoporotic vertebral compression fractures (OVCF) by targeting NDUFA4 and modulating the PI3K/AKT signaling pathway. These findings provide new insights into the molecular mechanisms underlying the progression of osteoporotic vertebral fractures.